2006
DOI: 10.1002/app.24041
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gas separation properties by using nanostructured PES‐Zeolite 4A mixed matrix membranes

Abstract: ABSTRACT:The polymer-zeolite mixed matrix membranes were fabricated by incorporating nanosized or microsized zeolite 4A into polyethersulfone. A comparison of zeolite 4A nanocrystals and microcrystals was made by using SEM, XRD, N 2 adsorption-desorption measurements. Zeolite particles were well-distributed in the polymer phase, as reflected by the SEM images. The effects of the zeolite 4A particle size on the gas permeation performance were studied. Experimental results demonstrate that mixed matrix membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 18 publications
(17 reference statements)
4
74
2
Order By: Relevance
“…%. This is because of polymer chain rigidification around the zeolite particles, partial pore blockage of zeolites by the polymer chains and extended diffusion pathways of the penetrants through the membrane [51][52][53][54][55], with constant or decreasing selectivity [23]. This behavior is attributed to the molecular sieving effect imparted by the introduction of the small-pore zeolites in the membrane, as well as the good interaction with the PTMSP chains that prevents interfacial voids.…”
Section: Influence Of Temperature On Transport Propertiesmentioning
confidence: 99%
“…%. This is because of polymer chain rigidification around the zeolite particles, partial pore blockage of zeolites by the polymer chains and extended diffusion pathways of the penetrants through the membrane [51][52][53][54][55], with constant or decreasing selectivity [23]. This behavior is attributed to the molecular sieving effect imparted by the introduction of the small-pore zeolites in the membrane, as well as the good interaction with the PTMSP chains that prevents interfacial voids.…”
Section: Influence Of Temperature On Transport Propertiesmentioning
confidence: 99%
“…A decrease in permeability was frequently observed that can be attributed to increased rigidity of polymer chains in the presence of zeolite particles (Huang, Li, Wen, Teoh, & Kulprathipanja, 2006;Moore & Koros, 2005), partial blockage of zeolite pores by polymer chains (Li, Chung, Cao, & Kulprathipanja, 2005), and/or extended diffusion pathways of hydrogen molecules through the membrane (Li et al, 2005;Li, Guan, Chung, & Kulprathipanjana, 2006;S€ uer, Baç, & Yilmaz, 1994). Polycarbonate loaded with 30 wt% highly crystalline zeolite-4A particles of 3 mm reached an H 2 /N 2 selectivity of 73, 30% higher than neat polycarbonate (Ş en, KalipçIlar, & Yilmaz, 2007).…”
Section: Hybrid Materialsmentioning
confidence: 93%
“…In the fabrication of MMMs, the effect of particle sizes has been considered as an important factor affecting the separation performances of resulting membranes [194,195] . In the most of early studies relating to zeolite/polymer MMMs, commercially available large particles were used as inorganic fi llers.…”
Section: Zeolite Fillers Fimentioning
confidence: 99%